1989
DOI: 10.1073/pnas.86.1.282
|View full text |Cite
|
Sign up to set email alerts
|

B-lymphoma cells process and present their endogenous immunoglobulin to major histocompatibility complex-restricted T cells.

Abstract: Antigen-presenting B-lymphoma cells were transfected with the gene encoding the immunoglobulin A2 light chain of MOPC315 cells (A2315). The A2 chain is expressed on the cell surface of the transfectants together with the endogenous heavy chain. (4) and that this recognition was under H-2-linked immune response (Ir) gene control (5). The hypothesis has been supported and extended by later work (6-8). Similar ideas have recently been proposed by others (9, 10), and MHC-restricted T cells specific for idiotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 30 publications
2
139
1
Order By: Relevance
“…Previous reports have established that Ab must be internalized and processed before Ab-derived peptides can be presented [4][5][6]17]. Indeed, we demonstrate that T cell activation was abolished if the APC were treated with leupeptin or brefeldin A prior to incubation with CCR1-specific mAb.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous reports have established that Ab must be internalized and processed before Ab-derived peptides can be presented [4][5][6]17]. Indeed, we demonstrate that T cell activation was abolished if the APC were treated with leupeptin or brefeldin A prior to incubation with CCR1-specific mAb.…”
Section: Discussionmentioning
confidence: 50%
“…However, the experiment can be performed using mAb that specifically target each chemokine receptor. It is well established that Ab are taken up by APC, processed, and presented on MHC class II molecules to CD4 + T cells [4,5]. Moreover, the presentation is further enhanced if the antibodies bind to surface molecules that intersect the endocytic processing pathway, such as transferrin receptor [6] or DEC-205 [7].…”
Section: Introductionmentioning
confidence: 99%
“…B cells can serve as APC (10,ll); they can process surface monomeric immunoglobulin and present peptides derived from it in their surface class I1 MHC molecules (12)(13)(14).…”
Section: Nzb/w) Female Mouse (43) Inactivation Of Helper T Cells Prementioning
confidence: 99%
“…It was further demonstrated that B cells continuously processed their own BCR and constitutively presented Id-peptides on their MHC class II molecules [9][10][11] [12]. Thus, B cells express two types of Id: (1) conformational Id determinants expressed on intact BCR, serologically detected by anti-Id antibodies and (2) short Id-peptides that are presented on MHC class II molecules to Id-specific T cells [9]. Id-peptide ⁄ MHC II presentation to CD4 + T cells represented at that time a novel type of interaction between T and B cells in the absence of external antigen, and it was suggested that such Id-driven T-B collaboration could play a role in immune regulation, autoimmunity and memory [13].…”
Section: Id-specific T Cells Recognize V-region Sequence Determinantsmentioning
confidence: 99%
“…In the 1980s it became clear that immunoglobulins are processed and presented by antigen-presenting cells (APC) and that V-region-derived Id-peptides are displayed on MHC class II molecules to Id-specific CD4 + T cells [5][6][7][8]. It was further demonstrated that B cells continuously processed their own BCR and constitutively presented Id-peptides on their MHC class II molecules [9][10][11] [12]. Thus, B cells express two types of Id: (1) conformational Id determinants expressed on intact BCR, serologically detected by anti-Id antibodies and (2) short Id-peptides that are presented on MHC class II molecules to Id-specific T cells [9].…”
Section: Id-specific T Cells Recognize V-region Sequence Determinantsmentioning
confidence: 99%